Thermal Decomposition of the Flame Retardant Tetrabromobisphenol A Bis(2,3-DibromopropylEther) - Philcox, A.; Ashman, P.; Buntine, Mark; Marney, D. (The Combustion Institute, 2010)
The thermal decomposition of the commonly used halogenated additive fire retardant, tetrabromobisphenol Abis(2,3-dibromopropyl ether) (PE-68) was studied in order to improve the understanding of its fire retardant chemistry. It is aimed to use this understanding in the formulation of a predictive tool that will ultimately encourage a mechanistic based approach to fire retardant selection and development. However, the interactions between flame retardant molecules and a polymer substrate under fire conditions are complex and difficult to characterise to the level of detail required to develop such a tool. Simplified experiments were used in this study to isolate some elements of the overall process. Specifically, flame retardant behaviour at high temperature was considered without the complication of a polymer substrate, and flame retardant decomposition was carried out in an inert atmosphere. Simultaneous thermogravimetric analysis and differential scanning calorimetry was conducted at a heating rate of10°C/min to investigate the pyrolysis of PE-68. A distinctive exothermic reaction was observed to occur between 290°C and325°C, with an enthalpy of approximately -30kJ/mol, which coincided with a weight loss of 55-60% of the initial mass of flame retardant. A one-step mechanism was proposed that agrees with both the thermogravimetric and calorimetric data. The validity of this mechanism was tested against the more common and more frequently studied parent compound of PE-68, tetrabromobisphenol A, with mixed results.